Online surveys as discourse context: Response practices and recipient design. (December 2020) - Raclaw, Joshua; Barchas-Lichtenstein, Jena; Bajuniemi, Abby
Abstract: While a growing body of work has focused on the interactional organization of telephone survey interviews, little if any research in conversation and discourse analysis has examined written online surveys as a form of talk-in-interaction. While survey researchers routinely examine such responses using content analysis or thematic analysis methods, this shifts the focus away from the precise language and turn constructional practices used by respondents. By contrast, in this study we examine open-ended text responses to online survey questions using a conversation analytic and discourse analytic approach. Focusing on the precise turn constructional practices used by survey respondents—specifically, how they formulate multi-unit responses and make use of turn-initial discourse markers—we demonstrate how online survey respondents treat open-ended survey questions much as they would any similar sequence of interaction in face-to-face or telephone survey talk, making online surveys a tenable source of data for further conversation analytic inquiry.